Asian flush is a potential protective factor against COVID-19: a web-based retrospective survey in Japan - Satoshi Takashima; Mikiko Tokiya; Katsura Izui; Hiroshi Miyamoto; Akiko Matsumoto (Komiyama Printing Co. Ltd, 2024)
Background: Coronavirus disease 2019 (COVID-19), first reported in December 2019, spread worldwide in a short period, resulting in numerous cases and associated deaths; however, the toll was relatively low in East Asia. A genetic polymorphism unique to East Asians, Aldehyde dehydrogenase 2 rs671, has been reported to confer protection against infections. Method: We retrospectively investigated the association between the surrogate marker of the rs671 variant, the skin flushing phenomenon after alcohol consumption, and the timing of COVID-19 incidence using a web-based survey tool to test any protective effects of rs671 against COVID-19. Results: A total of 807 valid responses were received from 362 non-flushers and 445 flushers. During the 42 months, from 12/1/2019 to 5/31/2023, 40.6% of non-flushers and 35.7% of flushers experienced COVID-19. Flushers tended to have a later onset (Spearman's partial rank correlation test, p = 0.057, adjusted for sex and age). Similarly, 2.5% of non-flushers and 0.5% of flushers were hospitalized because of COVID-19. Survival analysis estimated lower risks of COVID-19 and associated hospitalization among flushers (p = 0.03 and <0.01, respectively; generalized Wilcoxon test). With the Cox proportional hazards model covering 21 months till 8/31/2021, when approximately half of the Japanese population had received two doses of COVID-19 vaccine, the hazard ratio (95% confidence interval) of COVID-19 incidence was estimated to be 0.21 (0.10-0.46) for flusher versus non-flusher, with adjustment for sex, age, steroid use, and area of residence. Conclusions: Our study suggests an association between the flushing phenomenon after drinking and a decreased risk of COVID-19 morbidity and hospitalization, suggesting that the rs671 variant is a protective factor. This study provides valuable information for infection control and helps understand the unique constitutional diversity of East Asians.